STRATEGI PEMECAHAN MASALAH DALAM MATEMATIKA - Karsoni Berta Dinata (Eksponen, 2017)
The main purpose of studying mathematics is to find ways to solve problems or mathematics problems. What is meant by problems or mathematics problems is a thing that final result, or how to solve it is not known. In solving mathematical problems there are several strategies that can be used that are: direct proof, indirect proof, verification with contradiction, proof with examples of denying, reverse working strategy, pattern discovery, and the use of bird house principles.